Microwave-Assisted Sample Preparation for Simultaneous Determination of Trace Elements in Vegan Foods with Inductively Coupled Plasma Mass Spectrometry - Sel, Sabriye; Koyuncu, Ikbal (SPRINGER, 2025)
In this study, a new sample preparation methodology was applied to facilitate the accurate and precise determination of 12 selected elements in vegan food samples. Vegan foods (soy granules, egg substitute, puffed rice chocolate, oat nut chocolate, meatball mix, cheese, meat, chocolate vegan wafer, chips, sausage, butter, almond milk, soy milk, coconut milk, oat milk) were digested in a closed-vessel microwave system using various HNO3 and H2O2 combinations. The arsenic, barium, cadmium, cobalt, chromium, copper, iron, manganese, lead, nickel, vanadium, and zinc in vegan foods were determined by inductively coupled plasma mass spectrometry. The NIST 1515 (apple leaves) and NIST 1573A (tomato leaves) certified reference materials were used as test samples to optimize the digestion, and validate the trueness of the procedure using the certified values. The limits of detection calculated for the 12 elements were in the range of 0.010-0.042 ng mL-1, and the corresponding limits of quantification were in the range of 0.030-0.140 ng mL-1. Nine out of the twelve selected elements were detected in vegan samples digested with 14 mol L-1 HNO3 + H2O2 with the mass fractions ranging between 0.03 and 43 mu g g-1. Toxic elements such as As, Cd, and Pb were detected below the detection limits in all vegan samples. The aim of this study is to investigate by using ICP-MS the effect of different HNO3 + H2O2 combinations on the amounts of trace elements in such a number of such diverse vegan foods.
Keywords: Inorganic analytes; Nutrition profile; Vegan food; Potential toxic elements by microwave digestion; ICP-MS; GRAPHITE-FURNACE; ACID DIGESTION; EXTRACTION; METALS; VALIDATION; WASTE; ZINC; IRON; ZN; Food Science & Technology